Futureproof : how to get your business ready for the next disruption - Dial, Minter; Storkey, Caleb (Pearson Education Limited, 2017)
Futureproof paints a complete picture of the major disruptive forces currently facing us - defining them, mapping them out and putting them into context. Covering not just the new technologies, but how they are used and related, this book provides a global view of how to navigate the disruptive forces and use them to your advantage.